Plan de emprendimiento: portal informativo destino Perú - Lavado Gagliardi, Eduardo Julian (2024)
This Entrepreneurship Plan is developed around a Tourism sector in Perú that needs to recover spaces of visibility after the COVID-19 pandemic. It also seeks to develop a platform that, in an experienced and dynamic way, offers valuable content about the tourist attractions of Peru that can attract both the issuing sector (agencies, unions, hotels, airlines, among others) and the final audience (potential peruvian traveler who wants to enjoy his country). To this end, it is proposed to develop an alliance with the main tourism union (CANATUR) so that it can provide the support of its institution to operate both its platforms and the one that is the object of this project (Destino Perú), thereby generating differential products that enhance each other and that become an alternative for the development of attractive content for the entire sector, but at the same time constitute a vehicle for promoting destinations and services, and an opportunity to generate income for both institutions through the generation of sponsored content, guidelines advertising and activations on social networks.